Enhanced retention of a maxillofacial prosthetic obturator using precision attachments: Two case reports - Murat, Sema; Gurbuz, Ayhan; Isayev, Abulfaz; Dokmez, Bahadir; Cetin, Unsun (European Journal of Dentistry, 2012)
The majority of maxillary defects can be rehabilitated with conventional simple obturator prosthesis. However, inadequate retention, stability and support may be associated with the use of an obturator. Precision attachments have been used to retain obturators for some time. The use of precision attachments in a dentate maxillectomy patient can yield significant functional improvement while maintaining the obturator’s aesthetic advantages. This clinical report describes the prosthetic rehabilitation of two maxillary defects with an obturator retained using extracoronal resilient precision attachments. (Eur J Dent 2012;6:212-217)
Keywords: Obturator; retention; precision attachment